Second language speech comprehensibility. (October 2022) - Crowther, Dustin; Holden, Daniel; Urada, Kristen
Abstract : Published in Language Learning in 1995, Munro and Derwing's* investigation of foreign accent, comprehensibility, and intelligibility in second language (L2) speech instigated significant change in L2 pronunciation research (Levis, 2020). A key finding was that despite the presence of a foreign accent, listeners could indeed comprehend L2 speech. Within their framework, comprehension of L2 speech was assessed along two dimensions. The first, intelligibility, was an assessment of actual listener comprehension, measured through listener transcriptions of a given utterance. The second, comprehensibility, was a scalar measure of how easy to understand listeners perceived an utterance to be. While these two measures of listener comprehension (i.e., understanding) have been shown to correlate, they have also been shown to measure different forms of understanding (Derwing & Munro, 2015). This means that while increased intelligibility can be associated with increased comprehensibility, it is still common for listeners to accurately transcribe nonnative speech while simultaneously indicating the speech to be hard to understand (i.e., evidence indicates that intelligibility outpaces comprehensibility in the development of L2 pronunciation). Research published in the 25 years since has repeatedly demonstrated that accentedness, comprehensibility, and intelligibility are partially independent dimensions of L2 speech (Munro & Derwing, 2020). Whereas Munro and Derwing's (2011) research timeline attended to the concepts of accent and broad intelligibility (i.e., inclusive of both actual and ease of understanding), the past decade has seen an increased scholarly emphasis specifically on the global speech dimension of comprehensibility . Given this increased scholarly interest, our timeline is presented with the goal of tracing the post-Munro and Derwing (1995) development of L2 speech comprehensibility research.